2020
DOI: 10.1111/1750-3841.15334
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of rice as a suitable alternative for the production of ogi (a cereal‐based starchy fermented gruel)

Abstract: In the present study, the physicochemical and sensory properties of ogi (a cereal‐based starchy fermented gruel) produced from two local rice varieties, Abakaliki and Tapa, were determined. Ogi from white maize served as the control. There was a gradual increase in temperature from approximately 28 to 30 °C during fermentation. White maize exhibited the highest acidity level throughout the fermentation period. Tapa and Abakaliki rice ogi samples (i.e., TRO and ARO, respectively) were higher in yields and amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The pH was examined in the range of 4.22 to 5.08, as shown in Table 1. The result obtained was similar to the report of Akintayo et al [28], who reported a range of 4.91 to 5.56, and also similar to a report by Frederick et al [29], which recommends an equilibrium pH value of 4.6 or below as a safe pH for the preservation of finished product this is because, the lower the pH, the higher the level of acidity but slightly better than those gotten. The pH of the solardried Ogi reported was within the range of 4.6 to 5.1.…”
Section: Ph Of Ogisupporting
confidence: 91%
“…The pH was examined in the range of 4.22 to 5.08, as shown in Table 1. The result obtained was similar to the report of Akintayo et al [28], who reported a range of 4.91 to 5.56, and also similar to a report by Frederick et al [29], which recommends an equilibrium pH value of 4.6 or below as a safe pH for the preservation of finished product this is because, the lower the pH, the higher the level of acidity but slightly better than those gotten. The pH of the solardried Ogi reported was within the range of 4.6 to 5.1.…”
Section: Ph Of Ogisupporting
confidence: 91%
“…The CIE L* a* b* colour determination was adopted using the procedure described by Akintayo et al (2020) to analyse the colour of the ogi flour samples and it was evaluated objectively using a colorimeter. The colorimeter operates on the International Commission on Illumination (CIE) L*, a* and b* where L* indicates "lightness" (axis: 0 is black, 100 is white), a* means "red-green" (axis: positive values are red, negative values are green and 0 is neutral), b* indicates "yellow-blue" (axis: positive values are yellow, negative values are blue and 0 is neutral).…”
Section: Determination Of Colormentioning
confidence: 99%
“…Trough viscosity values for the maize ogi and spiced maize ogi samples as presented in Table 7 ranged between 1705.50±7.77 to 2127.50±38.89 RVU. The trough is a significant pasting parameter for starchy foods that typically undergoes an extended period of constant temperature after reaching their peak viscosity (Akintayo et al, 2020).…”
Section: Pasting Properties Of Maize Ogi Samples With Inclusion Of Gi...mentioning
confidence: 99%
“…Chinese rice wine starter is a complex mixture of hundreds of flavor compounds, including volatile aromatic compounds that arise from raw materials and from products of microbial metabolism that are present in the different brewing processes (Chen & Xu, 2013;Fei et al, 2011). Akintayo, Hashim, Adereti, Balogun, and Alabi (2020) found that rice has the potential to produce a fermented gruel that is more accepted by consumers than sample from maize. Previous studies have shown that rice wine starter can increase the content of phenolics and antioxidant activity of wine (Cai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%